The decision making process of consumers in relation to private labels: the specific case of yogurts in Portugal - Mendes, Pedro Mª da Cunha Policarpo Ferreira (2014)
Over the last few decades, private labels have grown and become an important competitive force on the marketplace. The general consumer of fast-moving consumer goods has changed his shopping habits and, now worries more about what he buys for the supply of his household. The economic crisis and the great amounts of information retailers provided about these products accelerated the success of these brands. As store brands grew, so did the academic and managerial interest in them. Throughout the past literature we see various researches on the determinants for the success of private labels and the key characteristics consumers take into account when selecting a brand. This study aims to point out the determinant factors that lead consumers to select private label goods in a specific industry, the Portuguese yogurt market. This is a thriving industry for store brands in Portugal, reaching almost half of the total market share.